Carbon nanotube-based aptasensor for sensitive electrochemical detection of whole-cell Salmonella - Hasan, Md Rakibul; Pulingam, Thiruchelvi; Appaturi, Jimmy Nelson; Zifruddin, Anis Nadyra; Teh, Swe Jyan; Lim, Teck Wei; Ibrahim, Fatimah; Leo, Bey Fen; Thong, Kwai Lin (Elsevier, 2018)
In this study, an amino-modified aptasensor using multi-walled carbon nanotubes (MWCNTs)-deposited ITO electrode was prepared and evaluated for the detection of pathogenic Salmonella bacteria. An amino-modified aptamer (ssDNA) which binds selectively to whole-cell Salmonella was immobilised on the COOH-rich MWCNTs to produce the ssDNA/MWCNT/ITO electrode. The morphology of the MWCNT before and after interaction with the aptamers were observed using scanning electron microscopy (SEM). Cyclic voltammetry and electrochemical impedance spectroscopy techniques were used to investigate the electrochemical properties and conductivity of the aptasensor. The results showed that the impedance measured at the ssDNA/MWCNT/ITO electrode surface increased after exposure to Salmonella cells, which indicated successful binding of Salmonella on the aptamer-functionalised surface. The developed ssDNA/MWCNT/ITO aptasensor was stable and maintained linearity when the scan rate was increased from 10 mV s−1 to 90 mV s−1. The detection limit of the ssDNA/MWCNT/ITO aptasensor, determined from the sensitivity analysis, was found to be 5.5 × 101 cfu mL−1 and 6.7 × 101 cfu mL−1 for S. Enteritidis and S. Typhimurium, respectively. The specificity test demonstrated that Salmonella bound specifically to the ssDNA/MWCNT/ITO aptasensor surface, when compared with non-Salmonella spp. The prepared aptasensor was successfully applied for the detection of Salmonella in food samples.